PEMANFAATAN VIRTUAL REALITY SEBAGAI PENDUKUNG PEMBELAJARAN INKLUSIF: STUDI KASUS SISWA BERKEBUTUHAN KHUSUS SPEKTRUM SLOW LEARNER - Sugiyanto, Sugiyanto; Sukesi, Keppi; Pintakami, Lintar Brillian; Satriawan, Pravasta Wahyu (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
This study aims to explore the potential of using Virtual Reality technology to enhance inclusive learning for students with special needs on the slow learning spectrum. The case study was carried out purposively at SMP Negeri 7 Pasuruan City, with the consideration that Pasuruan City was the first city in East Java to be declared an Inclusion City and was a pilot city for inclusion in Southeast Asia. The method of implementing community service used is in the form of outreach, training, and mentoring of students and teachers. Data collection methods used in this activity are observation and interviews. The data obtained were analyzed qualitatively. The results showed that the level of use of virtual reality tools by inclusive students was included in the high category with a score of 105 which had a percentage of 70%, meaning that inclusive students liked the use of virtual reality media in the learning process. The readiness to teach inclusive teachers is in the very high category with a score of 94 which has a percentage of 94%, meaning that inclusive teachers are very ready to teach or guide inclusive children in schools. In this study it is also seen that the use of Virtual Reality provides a more enjoyable learning experience for students with special needs. Teachers also felt a change in the level of student participation and their level of involvement in learning. From the results of this study, it can be concluded that Virtual Reality technology has great potential in helping improve inclusive learning for students with special needs on the slow learning spectrum. The use of this technology needs to be increased in the development of inclusive learning programs so that it can help students get a more enjoyable and effective learning experience